Using audio lures to improve golden‐winged warbler (Vermivora chrysoptera) detection during point‐count surveys. (14th April 2014) - McNeil, Darin J.; Otto, Clint R. V.; Roloff, Gary J.
ABSTRACT The golden‐winged warbler (Vermivora chrysoptera) is a Neotropical migratory songbird listed as a "Bird of Conservation Concern" by the U.S. Fish and Wildlife Service. To manage golden‐winged warblers, it is important to develop effective survey techniques for conservation research and monitoring. We conducted point counts in 1–8‐year‐old aspen (Populus sp.) stands in the northern Lower Peninsula of Michigan (USA), during 2011, to estimate detection probability of golden‐winged warblers, with and without an electronic broadcast of a golden‐winged warbler song (i.e., audio lure). We compared audio lure effectiveness for detecting golden‐winged warblers during fixed‐ (50‐m radius) and variable‐radius point counts. Golden‐winged warbler detection estimates were <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fbc5t8w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />P¯ˆ</alternatives> = 0.84 (95% CI = 0.39–0.98) and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fbc5t7b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />P¯ˆ</alternatives> = 0.22 (0.11–0.40) for fixed‐radius point counts, with and without audio lure, respectively. For variable‐radius point counts, golden‐winged warbler detection estimates were <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fbc5t6s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />P¯ˆ</alternatives> = 0.79 (CI = 0.51–0.93) and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh1fbc5t57" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />P¯ˆ</alternatives> = 0.57 (0.42–0.71), with and without audio lure, respectively. We also estimated the number of 3‐minute sub‐counts required to achieve detection probability ≥95% for both radii, with and without audio lures. We found that 2 sub‐counts with audio lure resulted in >95% detection probability for golden‐winged warblers at both radii. Without audio lure, 12 and 4 sub‐counts were required for fixed and variable radii, respectively. Regardless of survey technique, golden‐winged warbler detection probability was always <1.0, which highlights the importance of accounting for imperfect detection of golden‐winged warblers. Our results indicate that the use of an audio lure is an effective design technique for improving detectability of golden‐winged warblers. © 2014 The Wildlife Society.